Turkish Cypriot Economy : Looking Ahead to Steer the Economy Toward a Higher Growth Path - World Bank (World Bank, Washington, DC, 2020)
Following an unprecedented exchange-rate depreciation in 2018 that hammered both the Turkish and the Turkish Cypriot (TC) economies, the previous economic recovery in the TC economy collapsed. The fiscal deficit continued to shrink as the TC administration reduced expenditure due to declining budget support from Turkey. Looking ahead and doing things differently will help break this downward trend in income per capita and avoid widening the gap between TC income per capita and the European Union (EU). This will require investing more in higher-quality physical assets by changing the business model both in the public and private sectors; improving the quality of human assets by addressing both the technical and socio-emotional skills gaps, and inefficiencies in the education system; improving labor force participation by facilitating access to work opportunities for youth and women; and enhancing firms’ productivity by upgrading the business environment and reducing inefficient use of resources. Using the World Bank long-term growth model, the simulations show that the real income per capita of TC can double from between now and 2035 if investment in high-quality physical assets increases. Setting the TC economy on a high growth path and boosting its resilience to shocks will require reducing the economy’s dependence on imported fuel and diversifying toward renewable energy (RE). This macroeconomic monitoring note is structured in two chapters. Chapter one discusses recent economic developments and the short-term outlook, lays out the challenges to long-term growth that hold back income per-capita growth and presents policy recommendations to break the trend so that the TC economy can double its income per capita in the coming 15 years. Chapter two, the special issue, discusses how the TC economy can strengthen its resilience to help shield the economy from shocks, protect the most vulnerable, and ensure that incomes can rebound quickly.